Rupture Nucleation on a Periodically Heterogeneous Interface. Issue 20 (17th October 2022) - Gounon, A.; Latour, S.; Letort, J.; El Arem, S.
Abstract: In this study we explore experimentally the effects of fault heterogeneity on the rupture nucleation. We conducted friction experiments between two polycarbonate plates, with a periodically heterogeneous friction interface. The rupture propagation is monitored with an ultra‐fast video camera by taking advantage of the photo‐elastic properties of the material used. We show that the nucleation process does not always consists of a monotonic growth of the rupture velocity. Instead, the rupture front advances with an alternation of slow and fast episodes that accelerates until it reaches a point at which fast propagation dominates. This complex nucleation process is compared to the results predicted by previous numerical studies on heterogeneous interfaces. Finally, we test whether it is possible to describe this complex nucleation process as a homogenized nucleation. We also point out a large variability in the rupture process due to the uncontrolled stress heterogeneity that occurs during the loading process. Plain Language Summary: Measurements of earth surface deformation and of small intensity seismicity suggest that some large earthquakes are preceded by slow preparatory processes. Independently, several laboratory experiments, by sliding two blocks of rocks or plastic against one‐another, have shown that the slip begins with a so‐called initiation phase, during which the slipping area slowly grows until it reaches a size at which it accelerates and produces seismic waves. Whether this kind of initiation process is relevant for earthquakes is debated because these processes have been observed on homogeneous interfaces, very different from natural heterogeneous faults. To address this discrepancy, we mimicked earthquakes in the laboratory by sliding two blocks of plastic against one‐another, and observed the slip initiation with an ultra‐fast camera. We created an alternation of rough and smooth areas at the interface by roughening them with two different kinds of sandpaper. We observed a complex initiation process that consists of an accelerating alternation of slow and rapid episodes that enlarge the slipping area until the final large and fast rupture is triggered. These observations suggest that, on real faults, slow slip and seismic precursors could both be related as parts of a global complex initiation process. Key Points: We provide experimental observations of rupture nucleation on a periodically heterogeneous interface in mode II We observe in some cases an alternation of fast and slow rupture episodes correlated to the position of the heterogeneity Despite the rupture velocity changes at small scale, the nucleation is a globally accelerating process at larger scale